Parents' Attributions for Negative and Positive Child Behavior in Relation to Parenting and Child Problems. (21st December 2018) - Park, Joanne L.; Johnston, Charlotte; Colalillo, Sara; Williamson, David
Abstract : Previous research has stressed the importance of parents' attributions and parenting for child problems. Based on social cognitive models, studies have focused on the interrelations among parents' child-responsibility attributions for negative behavior, harsh parenting, and child problems. Little is known about the extent to which child-responsibility attributions for positive behavior and other types of parenting play a role in these models. The purpose of this study was to examine whether parents' child-responsibility attributions for positive and negative child behaviors are related to child problems, and whether these relations are mediated by harsh, lax, and positive parenting. Mothers' and fathers' attributions and parenting were examined separately. A community sample of 148 couples and their 9- to 12-year-old child (50% boys) participated in the study. Mothers and children participated by completing questionnaires and a laboratory interaction task. Fathers participated by completing the same questionnaires as mothers. Harsh parenting was the only parenting variable that uniquely mediated the relations between more child-responsibility attributions for (a) negative child behaviors and child problems for both parents and (b) the inverse relation between attributions for positive child behaviors and child problems for fathers. Findings confirm the importance of harsh parenting and demonstrate the importance of parents' attributions for positive child behaviors in relation to decreasing harsh parenting and child problems. Clinically, it may be useful not only to reduce child-responsibility attributions for negative behaviors but also to increase the extent to which parents give their child credit for positive behaviors.